2008
DOI: 10.1111/j.1751-2980.2008.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of lymph‐node metastasis in 1389 patients with early gastric cancer: Assessment of indications for endoscopic resection

Abstract: This large series of patients with EGC provides further evidence supporting the expansion of indications for endoscopic treatment, as well as warns against potential risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
3
17
1
Order By: Relevance
“…13 Therefore, a thorough, large-scale analytical study was needed to have more definitive evidence of the metastatic rate. There has been no study larger than the current study to clarify the risk factors for LNM in MGC, and although several studies have been reported for mucosal EGC [14][15][16] (Table 4), they were not consecutive or the extent of LND was not described. 3 Second, the identification of LNM was closely related with the number of harvested lymph nodes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 55%
“…13 Therefore, a thorough, large-scale analytical study was needed to have more definitive evidence of the metastatic rate. There has been no study larger than the current study to clarify the risk factors for LNM in MGC, and although several studies have been reported for mucosal EGC [14][15][16] (Table 4), they were not consecutive or the extent of LND was not described. 3 Second, the identification of LNM was closely related with the number of harvested lymph nodes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 55%
“…Nowadays, the extent of gastrectomy and lymph node dissection in gastric cancer were controversial, and some new operative methods, such as laparoscopic gastrectomy, endoscopic resection [12], which have minimal or no lymph nodes dissection, were introduced. The histological type should be an important factor when doctor select an optimal extent of gastrectomy and lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported the incidence of lymphatic involvement in intramucosal cancers and cancers that involved submucosal invasion altogether. Other reports showed lymph node metastasis in patients who had intramucosal gastric cancer [3,4,13,14,24]. Some authors suggested that lymphatic involvement was a risk factor for lymph node metastasis, but these studies evaluated lymphatic involvement irrespective of other risk factors, such as histological types (differentiated vs. undifferentiated), presence/absence of ulcer or tumor size.…”
Section: Discussionmentioning
confidence: 98%
“…In intramucosal cancers, lymph node metastasis was reported to be much less frequent, ranging from 1.9-3.3 %, compared to those in submucosal cancers, about 16.3-20.9 % [11][12][13][14][15]23]. A number of studies reported the incidence of lymphatic involvement in intramucosal cancers and cancers that involved submucosal invasion altogether.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation